LITERATURE REVIEW: PERAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DALAM MEDIA SOSIAL - Yusup, Ainiyah Hidayanti; Azizah, Asma; Rejeki, Endang Sri; Silviani, Meliza; Mujahidin, Ending; Hartono6, Rudi (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2023)
Technological developments, especially in the Society 5.0, offer connectivity between humans, machines and the environment, enabling intelligent and adaptive systems. Augmented Reality (AR) based learning media has great potential in bringing more interactive and effective learning. Unfortunately, the use of augmented reality (AR) in learning is usually limited to the form of flash cards or modules. An innovative utilization of AR-based learning media in social media platforms is expected to create an inclusive and attractive learning environment for the digital generation. This study aims to review scientifically the role of augmented reality-based learning media in media sosial. The benefit of this research is to assist stakeholders in the field of education in utilizing AR technology and integrate it with media sosial platforms to create an inclusive, accessible and attractive learning environment for the current digital generation. The research method used is the library research method or commonly known as Library Research. Data collection techniques use secondary data, in the form of documentation, existing research results, supporting books and articles. This study was compiled by the researcher using a mix of up-to-date and relevant books and journals chosen by the researcher. The results of the study show that the integration of Augmented Reality (AR) technology as a learning medium with social media such as Instagram shows positive and effective results. Some filters that already use this technology can increase the motivation, interest and curiosity of learners. The learning target can also be wider, because it can be accessed by anyone, anytime, and anywhere with the support of adequate camera and smartphone specifications. The use of AR also does not limit what lessons will be covered, depending on the learning designer. ABSTRAKPerkembangan teknologi terutama era Society 5.0 menawarkan konektivitas antara manusia, mesin, dan lingkungan, memungkinkan sistem yang cerdas dan adaptif. Media pembelajaran berbasis Augmented Reality (AR) memiliki potensi besar dalam membawa pembelajaran yang lebih interaktif dan efektif. Penelitian ini bertujuan untuk meninjau secara ilmiah peranan media pembelajaran berbasis augmented reality dalam media sosial. Manfaat dari penelitian ini yaitu untuk membantu pihak-pihak yang berkepentingan dalam pendidikan dalam memanfaatkan teknologi AR dan memadukannya dengan platform media sosial untuk menciptakan lingkungan pembelajaran yang inklusif, aksesibel, dan menarik bagi generasi digital saat ini. Metode penelitian yang digunakan adalah metode riset pustaka atau yang biasa dikenal dengan Library Research. Teknik pengambilan data menggunakan data sekunder, yang berupa dokumentasi, hasil-hasil penelitian yang sudah ada, buku dan artikel yang mendukung. Penelitian ini disusun oleh peneliti menggunakan perpaduan antara buku dan jurnal yang  uptodate dan relevan pilihan peneliti. Hasil penelitian menunjukkan bahwa pemaduan teknologi Augmented Reality (AR) sebagai media pembelajaran dengan media sosial seperti instagram, menunjukkan hasil yang positif dan efektif. Beberapa filter yang sudah menggunakan teknologi ini dapat meningkatkan motivasi, minat dan rasa keingintahuan yang lebih dari peserta didik. Sasaran pembelajarannya pun bisa lebih luas, karena dapat diakses oleh siapapun, kapanpun, dan dimanapun dengan di support oleh kamera dan spesifikasi smartphone yang memadai. Penggunaan AR ini juga tidak membatasi pelajaran apa yang akan dibahas, bergantung pada pendesain pembelajaran tersebut